LEGISLATIVE SUPPORT OF TEACHER PROFESSIONAL DEVELOPMENT IN UKRAINE - Кирил Котун (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
Modern education acquires qualitative transformations, adapting to new conditions. Institutions of postgraduate pedagogical education and methodological services are undergoing a thorough reorientation, to overcome a number of stereotypes in the system of teacher professional development before calling for educational services to improve the skills of newly established professional educational associations and NGOs. However, today not only is the problem of inconsistency of the current education system with new needs exacerbated, but also traditions and connections are being broken. Therefore, it is necessary to maintain cooperation between educational institutions and build new cooperation with communities in the regions, without losing the potential of institutions of postgraduate pedagogical education. The New Ukrainian School is changing the entire education system and the teacher, who must be an agent of change, a provider of educational reform, a community leader. These changes affect the system of postgraduate education, causing a new content and technological burden on the teacher professional development. The basis of teacher professional development is the awareness of all transformations in education as a natural need to constantly improve their skills, to form and develop a professional worldview and pedagogical consciousness. The ar-ticle outlines the features of legislative support for the teacher professional development in Ukraine. Several ways of implementing parts of the new law of Ukraine "On Education" on teacher professional development are substantiated (for example, change of forms of teacher professional development, change of mentality, financing of professional development, formation of a plan of teacher professional development etc.). The functional activities of the future Centres for Teacher Professional Development, which will replace the current methodical offices, as well as the concept of "professional development" are briefly outlined.